Social Skills and Resilience in Adolescents of an Educational Institution in North Lima, 2019 - Sifuentes Gomez, Lili Julita (2020)
Social skills are a set of partially independent and situationally specific verbal or nonverbal responses, in terms of resilience, it is the set of qualities, resources or strengths that favor adolescents to face the adversities of life, therefore the objective of the research work is to determine the social skills and resilience in adolescents of an educational institution in Lima - North. It is a non-experimental study, descriptive of a quantitative approach, it is a cross-sectional correlational research, with a population of 706 students of the secondary level, also with demographic data, and the Social Skills Scale (SSS), and the scale of Resilience (CD-RISC) that will measure the level of resilience of adolescents. The relationship between the variables Social Skills and Resilience. It was determined based on the Pearson's Chi square test (X2). The significance level of the test obtained a value 0.000 (p<0.05) (X2 = 28.626; g.l. = 4). So, the dissociation hypothesis is rejected and it can be affirmed with statistical evidence that there is a significant relationship between social skills and resilience. The predominant level of social skills is medium with 648 (91.8%) participants and in terms of resilience, the predominant level is high with 366 (51.8%) of participants. Social skills and resilience are mutually related since both allow the adolescent to face situations of daily life looking the ability to develop their coping capacity